2020
DOI: 10.1098/rstb.2019.0242
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic conservation of soil bacterial responses to simulated global changes

Abstract: Soil bacterial communities are altered by anthropogenic drivers such as climate change-related warming and fertilization. However, we lack a predictive understanding of how bacterial communities respond to such global changes. Here, we tested whether phylogenetic information might be more predictive of the response of bacterial taxa to some forms of global change than others. We analysed the composition of soil bacterial communities from perturbation experiments that simulated warming, drought, elevated CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 75 publications
3
58
1
Order By: Relevance
“…This was consistent with a methane oxidation mediated by microorganisms and in fact, next generation sequencing (NGS) analysis of sediments showed a relative abundance of Candidatus Methylomirabilis 4 to 5 times higher in the deepest sample (−80 m) with respect to −30 and −15 m. Candidatus Methylomirabilis oxyfera (Rokubacteria) is an anaerobic denitrifying methanotroph [46]. It must be noticed that Isobe et al [47] found that members of the uncultivated candidate phylum Rokubacteria responded positively to elevate CO 2 concentrations.…”
Section: The Control Of Greenhouse Gas Fluxes By Cave Microorganismssupporting
confidence: 77%
“…This was consistent with a methane oxidation mediated by microorganisms and in fact, next generation sequencing (NGS) analysis of sediments showed a relative abundance of Candidatus Methylomirabilis 4 to 5 times higher in the deepest sample (−80 m) with respect to −30 and −15 m. Candidatus Methylomirabilis oxyfera (Rokubacteria) is an anaerobic denitrifying methanotroph [46]. It must be noticed that Isobe et al [47] found that members of the uncultivated candidate phylum Rokubacteria responded positively to elevate CO 2 concentrations.…”
Section: The Control Of Greenhouse Gas Fluxes By Cave Microorganismssupporting
confidence: 77%
“…Microbes not only drive many important soil processes, they also respond to biotic and abiotic soil conditions. For example, consistent changes in soil microbial communities have been associated with changes in P availability (Hermans et al, 2017), soil pH (Delgado-Baquerizo et al, 2018), labile organic carbon pools (Ramírez et al, 2020), and soil moisture levels (Isobe et al, 2020). Likewise, we can often identify particular microbial taxa or functional genes associated with specific soil processes, including nitrification, methane production, denitrification, and cellulose degradation.…”
Section: Microbes As Bio-indicatorsmentioning
confidence: 99%
“…Thus, as the discovery of traits governing pyrophilous microbes’ fire response are uncovered, the ecological role of related microbes will be better predicted in future post-fire sampling. For example, bacterial response to both nitrogen addition (Isobe et al, 2019) and simulated global climate change factors was phylogenetically conserved across all perturbations (Isobe et al, 2020), which improves prediction of disturbance response of closely related taxa.…”
Section: Introductionmentioning
confidence: 99%